Colonic response to laxative ingestion as assessed by MRI differs in constipated irritable bowel syndrome compared to functional constipation. Issue 6 (12th February 2016) - Lam, C.; Chaddock, G.; Marciani, L.; Costigan, C.; Paul, J.; Cox, E.; Hoad, C.; Menys, A.; Pritchard, S.; Garsed, K.; Taylor, S.; Atkinson, D.; et al.
Abstract: Background: Functional constipation (FC) and irritable bowel syndrome with constipation (IBS‐C) share many symptoms but underlying mechanisms may be different. We have developed a magnetic resonance imaging (MRI) technique to measure intestinal volumes, transit, and motility in response to a laxative, Moviprep ® . We aim to use these biomarkers to study the pathophysiology in IBS‐C and FC. Methods: Twenty‐four FC and 24 IBS‐C were studied. Transit was assessed using the weighted average position score (WAPS) of five MRI marker pills, taken 24 h before MRI scanning. Following baseline scan, participants ingested 1 L of Moviprep ® followed by hourly scans. Magnetic resonance imaging parameters and bowel symptoms were scored from 0 to 4 h. Key Results: Weighted average position score for FC was 3.6 (2.5–4.2), significantly greater than IBS‐C at 2.0 (1.5–3.2), p = 0.01, indicating slower transit for FC. Functional constipation showed greater fasting small bowel water content, 83 (63–142) mL vs 39 (15–70) mL in IBS‐C, p < 0.01 and greater ascending colon volume (AC), 314 (101) mL vs 226 (71) mL in IBS‐C, p < 0.01. FC motility index was lower at 0.055 (0.044) compared to IBS‐C, 0.107 (0.070), p < 0.01. Time to first bowel movement following ingestion of Moviprep ® was greater for FC, being 295 (116–526) min, compared to IBS‐C at 84 (49–111) min, p < 0.01, and correlated with AC volume 2 h after Moviprep ®, r = 0.44, p < 0.01. Using a cut‐off >230 min distinguishes FC from IBS‐C with low sensitivity of 55% but high specificity of 95%. Conclusion & Inferences: Our objective MRI biomarkers allow a distinction between FC and IBS‐C. Abstract : The underlying disorder of function differs in FC and IBS‐C implying that response to treatments altering motility will differ. Using a stimulus such as Moviprep ®, FC can be differentiated from IBS‐C by assessing the motility of AC and time to first bowel movement, MRI can be used as a tool to clarify the underlying functional abnormality in patients with difficult and resistant constipation, Even without MRI, using 1 L of Moviprep ® as a stimulant and measuring the time to first bowel movement can assist in differentiating between FC and IBS‐C.